PROSES MANUFAKTUR MESIN PEMBUAT BATU BATA BERBAHAN PULP DENGAN KAPASITAS 20KG/PROSES - Raihan Hauzan Arrafii, (2021)
The amount of unused paper waste is one of the factors that can cause environmental damage. Paper recycling can not only help reduce environmental pollution, but also increase the selling value of the waste. Not all business actors can own a brick-making machine, especially Business, Micro, Small and Medium Enterprises (MSMEs), due to the high price and usually made on a large scale. This study aims to design a brick making machine made from pulp with a capacity of 20 kg/process with a horizontal blade type. The main material that will be used as paper bricks is pulp or what is commonly called paper pulp. From the results of the engine design, the engine capacity is ± 20 kg/process, with dimensions of 114 cm x 84 cm x 87 cm, and the motor power is 1.5 HP. The main components consist of horizontal blades, pneumatics, upper reservoirs, lower reservoirs, frames, molds, flow pipes, and drive units consisting of electric motors, belts, pulleys, shafts, and bearings. The result of testing the capacity of this machine is 20 kg/process, with a total of 60 paper bricks/hours, where each process takes 1 minute and produces 1 paper brick weighing 20 kg.